2007
DOI: 10.1080/13668250701402767
|View full text |Cite
|
Sign up to set email alerts
|

Comparing sexual offender treatment efficacy: Mainstream sexual offenders and sexual offenders with special needs

Abstract: There are a number of limitations to this study, particularly as a result of the experimental design and the small number of participants, and these should be considered as a major limitation on the conclusions drawn from the results. However, it is suggested that the program had some positive effects for some offenders, with little difference in progress detected between the two groups. Possible explanations for the varied outcomes are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 19 publications
0
52
0
Order By: Relevance
“…Six articles used multiple case study designs with baseline, post-treatment, and follow-up assessments (Craig et al, 2006; Lindsay, Marshall, Neilson, Quinn, & Smith, 1998; Lindsay, Neilson, Morrison, & Smith, 1998; Lindsay, Olley, Baillie, & Smith, 1999; Rose, Jenkins, O’Connor, Jones, & Felce, 2002; Sakdalan & Collier, 2012), and one multiple case study design was included with no follow-up assessment (Singh et al, 2011). Finally, three studies employed quasi-experimental designs (Keeling, Rose, & Beech, 2007; Lindsay, Michie, Steptoe, Moore, & Haut, 2011; Michie & Lindsay, 2012). Michie and Lindsay (2012) designed a study consisting of two groups of sex offenders with IDD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six articles used multiple case study designs with baseline, post-treatment, and follow-up assessments (Craig et al, 2006; Lindsay, Marshall, Neilson, Quinn, & Smith, 1998; Lindsay, Neilson, Morrison, & Smith, 1998; Lindsay, Olley, Baillie, & Smith, 1999; Rose, Jenkins, O’Connor, Jones, & Felce, 2002; Sakdalan & Collier, 2012), and one multiple case study design was included with no follow-up assessment (Singh et al, 2011). Finally, three studies employed quasi-experimental designs (Keeling, Rose, & Beech, 2007; Lindsay, Michie, Steptoe, Moore, & Haut, 2011; Michie & Lindsay, 2012). Michie and Lindsay (2012) designed a study consisting of two groups of sex offenders with IDD.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment programs for sex offenders with IDD were implemented in a variety of settings and nations including prisons, hospitals, assisted living arrangements, and private homes in the United Kingdom, the United States, New Zealand, and Australia. Twelve studies were conducted in the United Kingdom (Craig et al, 2006; Craig et al, 2012; Lindsay, Marshall, et al, 1998; Lindsay, Neilson, et al, 1998; Lindsay et al, 2011; Lindsay et al, 1999; Lindsay & Smith, 1998; Michie & Lindsay, 2012; Murphy et al, 2007; Murphy et al, 2010; Rose et al, 2002; Rose et al, 2012), three studies were conducted in Australia (Keeling et al, 2006b, 2007; O’Connor, 1996), two in the United States (Rea et al, 2014; Singh et al, 2011), and one in New Zealand (Sakdalan & Collier, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Offenders with ID are often classified based on their index offence, which is illustrated, for instance, in several papers focusing on specific offender types (e.g., Guay, Ouimet & Proulx, 2005;Keeling, Beech, & Rose, 2007c). This is undoubtedly one valuable way to create more homogenous offender groups for research or treatment purposes (e.g., Alexander, Crouch, Halstead, & Pischaud, 2006).…”
Section: Beyond the Iq Of The Offender: Challenging The Usefulness Ofmentioning
confidence: 99%
“…They concluded that shorter treatment periods may be of limited value for this group. Keeling, Rose, and Beech (2007) conducted another comparison of convenience between 11 ''special needs'' offenders and 11 mainstream offenders matched on level of risk, victim sex, offence type and age. The authors noted a number of limitations including the fact that ''special needs'' was not synonymous with ID and, as a result, they were unable to verify the intellectual differences between the mainstream and special needs populations.…”
Section: Inappropriate Sexual Behaviour and Sexual Offendingmentioning
confidence: 99%